2021
DOI: 10.1039/d0ra10125g
|View full text |Cite
|
Sign up to set email alerts
|

Restricted binding of a model protein on C3N4nanosheets suggests an adequate biocompatibility of the nanomaterial

Abstract: The fixed binding pattern of protein adsorption to C3N4 plays a major role in the nanomaterial biocompatibility, which results from the inherent porous surface structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, this mechanism should happened when there is a relatively large flat surface around the defect. The HP35 unfolding will not occur if the defects of the 2D nanomaterials are relatively close to each other, e.g., in phosphorene 49 , C 2 N 50 , C 3 N 4 51 , C 3 N 3 52 and in α-phase phosphorene carbide 55 . The defects on these nanomaterials usually contain local charges, attracting the residues of HP35 with opposite charges, by which the HP35 is fully fixed on one position and the lateral movement of the protein on 2D nanomaterials’ surface is restrained, thus the HP35 protein structure remains intact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this mechanism should happened when there is a relatively large flat surface around the defect. The HP35 unfolding will not occur if the defects of the 2D nanomaterials are relatively close to each other, e.g., in phosphorene 49 , C 2 N 50 , C 3 N 4 51 , C 3 N 3 52 and in α-phase phosphorene carbide 55 . The defects on these nanomaterials usually contain local charges, attracting the residues of HP35 with opposite charges, by which the HP35 is fully fixed on one position and the lateral movement of the protein on 2D nanomaterials’ surface is restrained, thus the HP35 protein structure remains intact.…”
Section: Resultsmentioning
confidence: 99%
“…HP35 has undergone extensive experimental and computational investigation regarding its folding and unfolding dynamics that has been helpful to better understand the protein folding problem 37 39 . More importantly, owing to these characteristics, various theoretical studies have extensively utilized this protein model to assess the potential biocompatibility of various nanomaterials at a from molecular level through its direct interaction 40 – 44 , with graphene 45 , defective graphene 46 , graphene quantum dots 47 , boron nitride 48 , phosphorene 49 , carbon nitride (C 2 N 50 , C 3 N 4 51 , C 3 N 3 52 and C 3 N 53 ), carbon boride (BC 3 ) 54 , and α-phase phosphorene carbide 55 , to mention a few. Researchers usually used the HP35 protein to investigate the possible protein unfolding on the nanomaterials’ surface, by which the potential bio-effect could be evaluated via observing the perturbations in the secondary and tertiary structure (i.e., unfolding) of this protein after adsorption onto the nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some residues (e.g., Lys 439, distance = 1.8 Å) on HSA were tightly captured by the inherent pores of CN (Figure b). Because the inherent pores of CN possess a high negative charge density, the −NH 3 groups on residues of HSA are easily adsorbed by these pores through electrostatic attraction …”
Section: Results and Discussionmentioning
confidence: 99%
“…Because the inherent pores of CN possess a high negative charge density, 19 the −NH 3 groups on residues of HSA are easily adsorbed by these pores through electrostatic attraction. 71 The influence of HSA coronas on the interaction of CN with RBCs and hence caused cytotoxicity was then investigated. However, as shown in Figure 5c, in the presence of HSA, the hemolysis was linearly reduced as HSA concentration increased, which was proved by an optical micrograph of RBCs in Figure 5d.…”
Section: Destructive Extraction Of Phospholipids From Cellmentioning
confidence: 99%
“…The structure of the C 3 N 3 material shares a similar porous nanostructure with C 3 N 4 and thus might present comparable physical and chemical features that could be exploited in bionanomedicine. In this context, previous studies have reported the interaction between proteins and some carbon nitride nanomaterials, such as C 3 N 4 40 , C 2 N 41 , and C 3 N 42 . However, there has been limited knowledge regarding the interaction of C 3 N 3 with biomolecules, even though this type of information is pivotal to assessing the bio-effect of the C 3 N 3 nanomaterial.…”
Section: Introductionmentioning
confidence: 96%